THE INFLUENCE OF GOOD CORPORATE GOVERNANCE TOWARDS COMPANY VALUE WITH PROFITABILITY AS INTERVENING VARIABLE IN MANUFACTURING COMPANIES - Florentia Tiurma Puspita Manik; Purwanto Purwanto (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Good corporate governance and profitability are efforts to increase company value. The company was established to increase the company value to provide prosperity for the owners or shareholders. This study aims to determine the effect of corporate governance on company value with profitability as an intervening variable in manufacturing industries in manufacturing companies. The data research is taken from the financial reports of 19 selected companies on the Indonesia Stock Exchange for 2015-2020 using quantitative research. The independent variables are proxied by institutional ownership, audit committee, managerial ownership, independent Board of Commissioners, and Board of Director. Return on equity is a proxy of the profitability as an intervening variable and Tobin's q as a dependent variable. The method of data analysis used in this research is multiple linear regression analysis using statistical software. The data results show that the independent Board of commissioners and directors significantly influences ROE. The other three variables are not significant in predicting ROE. The audit committee and independent panel of commissioners do not affect the company's value. On the other hand, company value is affected by institutional ownership, managerial ownership, and the Board of directors. Those five variables of good corporate governance and ROE simultaneously effectively predict company value with a 75.17% contribution. Profitability mediates the relation between good corporate governance and company value.